Design and fabrication of steering system for student formula race car / Muhammad Afiq Arpin - Arpin, Muhammad Afiq (2024)
The steering system plays an integral role in determining the car's handling, reactivity, and driver control. This project seeks to create a dependable and effective steering mechanism that boosts the overall performance of the race car. Elements like weight, strength, ergonomics and manufacturability must be considered in the design process. Examination of new ideas and technologies through extensive research improves the performance of the steering system. Precise 3D models are produced using the computer aided design, CAD program SolidWorks 2021. The fabrication process involves choosing materials of high quality. In order to guarantee accuracy and dependability, the steering system's components undergoes precise machining and welding processes. It aims to improve the handling, responsiveness, and general competitiveness of the car in racing events. An effective steering system design and production leads to successful achievement